Effect of Differentiated Learning Based Learning Style on Learning Outcome IV Grade in Mathematics - Komarudin, Komarudin; Putri, Dya Ayu Agustiana (Jurnal Didaktika Pendidikan Dasar, 2025)
Differentiated learning is a solution to the lack of attention to differences in learning styles among students, which results in unmet learning needs and suboptimal learning outcomes This study aims to examine the effect of different learning styles on the learning outcomes of fourth-grade elementary school students. The research method used is quantitative with a quasi-experimental design. The sample in this study consists of 31 fourth-grade elementary school students in Sendang Subdistrict, selected using purposive sampling. Data collection techniques used a test consisting of 20 multiple-choice questions based on cognitive levels C1-C6 of length measurement material. Data analysis used the Independent Sample T-Test. The research results showed that the p-value in the pretest and posttest was < 0.001, indicating a significant effect. This study concludes that differentiated instruction based on learning styles has a significant effect on the learning outcomes of fourth-grade students in mathematics. Differences in learning styles can be accommodated in the classroom learning process to meet the diverse needs of students and encourage high motivation to learn in order to achieve maximum academic results.